Functional strength exercise and blood-flow restriction protocols: a systematic review - Nicole J. Hernandez; Bradley J. Myers; Yuri Feito; Jennifer A. Bunn (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2020)
Objective: To assess current literature focused on the influence of functional training with blood flow restriction (BFR) on muscular adaptation in adults below the age of 65 years. Methods: A systematic literature search was performed with the following databases: PubMed, CINAHL Complete EBSCOhost, and ScienceDirect. Two researchers filtered the articles according to the criteria and quality, supported by the Consolidated Standards of Reporting Trials (CONSORT) tool. Studies were limited to those with participants with a mean age between18 and 65 years. Articles were peer-reviewed, available in English, and utilized either multi-joint resistance exercises or functional exercise as the intervention. Results: The search yielded 16 studies on uninjured, older adult, injured and athletic subjects. Regardless of the population, the studies tended to favor BFR training for improvements of strength, but this was highly dependent on cuff pressure and training load. Conclusions: Current literature suggests that BFR with functional and or multi-joint strength training is successful in improving strength, hypertrophy, function and in pain reduction. Favorable results with functional BFR included procedures using relative and well-controlled occlusion pressure. More research is necessary to understand the effect of BFR on self-reported outcomes and hypertrophy in athletic and older adults.